Waringin Sehat: Program Edukasi, Pencegahan, dan Akses Kesehatan Untuk Hidup Lebih Baik - Yus Alvar Saabighoot; Yusrafidin Yusrafidin; Rakhmini Juwita; Rizka Nurhalija; Rory Fitriani Larasati; Annisa Raudhatul Jannah; Lulu Ilmanunah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The problem of stunting and malnutrition in early childhood remains a serious challenge in Indonesia. Data shows a high prevalence of stunting, necessitating integrated and sustainable interventions. The